2016
DOI: 10.3390/foods5020041
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition of Essential Oils from Different Aromatic Herbs Grown in Mediterranean Regions of Spain

Abstract: Volatile composition of essential oils from dill, parsley, coriander, and mint were investigated at different harvest dates to determine the most suitable harvest time for each these herbs. Hydrodistillation (HD), using a Deryng system, was used for isolating the essential oils. Isolation and identification of the volatile compounds were performed using gas chromatography-mass spectrometry (GC-MS) instrument. The results of gas chromatography-flame ionization detector (GC-FID) analysis (quantification) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…In the case of many plant species of the families Lamiaceae, Poaceae and Asteraceae, leaf development has been shown to be closely correlated with essential oil biosynthesis and accumulation [Rehman et al 2016]. El-Zaeddi et al [2016] showed that harvest date and related plant age as well as plant developmental stage modify essential oil content and composition as well as sensory qualities of raw material. On average, the S. montana herb contained 0.42% of flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of many plant species of the families Lamiaceae, Poaceae and Asteraceae, leaf development has been shown to be closely correlated with essential oil biosynthesis and accumulation [Rehman et al 2016]. El-Zaeddi et al [2016] showed that harvest date and related plant age as well as plant developmental stage modify essential oil content and composition as well as sensory qualities of raw material. On average, the S. montana herb contained 0.42% of flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical polymorphism of EOs is characteristic to species of Thymus and Oregano (Kintzios, 2012;Ložienė & Venskutonis, 2005). It is well known that environmental factors such as temperature, moisture, the chemical composition of the soil, stage of vegetative cycle, and harvesting seasons influence the chemical composition of EOs (El-Zaeddi, Martínez-Tomé, Calín-Sánchez, Burló, & Carbonell-Barrachina, 2016;Ložienė & Venskutonis, 2005). Different chemical profile of EOs, for example, lack of the uniformity of EOs at the market at the moment present one of the main limiting factors for preservation purposes.…”
Section: Food Chemistrymentioning
confidence: 99%
“…2), which could have been attributable to ontogenetic variation. El-Zaeddi et al [2016] demonstrated changes in the content of some essential oil constituents (including limonene and myrcene) in leaves of fennel, coriander, parsley and mint harvested at different times. These authors report that proper harvest time of the abovementioned spice herbs is extremely important with regard to the essential oil content and sensory quality of the plant material.…”
Section: Resultsmentioning
confidence: 97%